Intellectual Brilliance Among Kindergarten Teachers and Its Relationship to Some Variables. - سالم, استبرق داود (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The aim of this research is to identify: Intellectual brilliance among kindergarten teachers. Differences between kindergarten teachers in intellectual brilliance based on years of service. Differences between kindergarten teachers in intellectual brilliance based on their specialization (kindergarten education vs. other specializations). To achieve the research objectives, the researcher developed a "Scale of Intellectual Brilliance" following the scientific steps for building psychological scales. The scale consists of 25 items and was administered to a sample of 100 kindergarten teachers from public kindergartens located in Al-Karkh Second district in Baghdad for the academic year (2024-2025). The researcher verified the psychometric properties of the scale, including validity and reliability. Validity was assessed using two methods: apparent validity and construct validity, while reliability was determined using the Cronbach’s alpha method, yielding a reliability coefficient of 0.89, which is considered adequate and statistically significant, Based on the research objectives, after applying the scales to the sample and statistically analyzing their responses using independent samples t-tests, Pearson correlation coefficient, phi coefficient, one-sample t-test, and one-way ANOVA, the researcher reached several findings: kindergarten teachers exhibit high intellectual brilliance, there are no statistically significant differences in intellectual brilliance based on years of service, and there are no statistically significant differences in intellectual brilliance based on specialization. In light of the research findings, the researcher concluded with a series of recommendations and suggestions.